Optimization of Naringenin Self-Nano Emulsifying Drug Delivery System (SNEDDS) Formula with D-optimal Mixture Design Method - Yudanti, Gendis Purno; Kuncahyo, Ilham; Ikasari, Endang Diyah (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2024)
This study aimed to optimize and formulate the poorly water-soluble naringenin in the Self-Nano Emulsifying Drug Delivery System (SNEDDS) using D-optimal mixture design. D-optimal mixture design was used to optimize SNEDDS loading naringenin by selecting SNEDDS composition as an independent factor and SNEDDS characterization as a response. SNEDDS in the optimal formula were characterized, including transmittance, particle size, emulsification time, and drug loading. Triacetin, Tween 80, and transcutol p were respectively the selected oil, surfactant, and co-surfactant phases for their greatest ability to dissolve naringenin. The optimization results showed that the optimal formula was that using 10% triacetin, 70% of Tween 80, and 20% of transcutol p. SNEDDS loading naringenin produced nanoemulsion with 88.74±2.27 % of transmittance, 14.8 nm of particle size, 51.13 ± 4.53 mg/L of drug loading, and 18.58 ± 0.62 second of emulsification time. This study concludes that the D-optimal mixture design can be used to optimize and prepare the SNEDDS loading poorly-water soluble naringenin.